Hubungan Usia dengan Stadium Saat Diagnosis Penderita Kanker Kolorektal di RSUD Abdul Wahab Sjahranie Samarinda: Relationship of Age and Stadium when Diagnosed of Cholorectal Cancer at RSUD Abdul Wahab Sjahranie Samarinda - Sri Jatul Zannah; Ignatia Sinta Murti; Sulistiawati Sulistiawati (Jurnal Sains dan Kesehatan, 2021)
Abstract Background: Colorectal cancer is a malignancy originating from the colon tissue. The incidence of colorectal cancer was recorded at 396,914 new cases with 234,511 deaths and the fourth rank of all types of cancer cases in Indonesia. This study aims to determine the relationship between age and histopathological features and stage when diagnosed with colorectal cancer at Abdul Wahab Sjahranie Hospital, Samarinda. Methods: The study design was retrospective analytic with a cross sectional study approach. The research data came from the medical records of colorectal cancer patients at Abdul Wahab Sjahranie Hospital, Samarinda in 2017-2020. Results: A total sample size of 71 samples. Data analysis statistically showed the relationship between age and stage at diagnosis with p = 0.004 (p = 0.05). Conclusion: The relationship between age and stage at diagnosis of colorectal cancer patients at Abdul Wahab Sjahranie Hospital, Samarinda. Keywords: Colorectal Cancer, Age, Stage